2023
DOI: 10.1038/s43018-023-00614-y
|View full text |Cite
|
Sign up to set email alerts
|

A first-in-class pan-lysyl oxidase inhibitor impairs stromal remodeling and enhances gemcitabine response and survival in pancreatic cancer

Abstract: The lysyl oxidase family represents a promising target in stromal targeting of solid tumors due to the importance of this family in crosslinking and stabilizing fibrillar collagens and its known role in tumor desmoplasia. Using small-molecule drug-design approaches, we generated and validated PXS-5505, a first-in-class highly selective and potent pan-lysyl oxidase inhibitor. We demonstrate in vitro and in vivo that pan-lysyl oxidase inhibition decreases chemotherapy-induced pancreatic tumor desmoplasia and sti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 62 publications
(94 reference statements)
0
3
0
Order By: Relevance
“…We hypothesized LOX activity may account for the increased vessel stiffness we observed in arterioles with CAA. A recent study using pan-lysyl oxidase inhibition in pancreatic cancer showed remodeling and crosslinking with fibrillar collagen matrices, reducing the tumor stiffness [14].…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized LOX activity may account for the increased vessel stiffness we observed in arterioles with CAA. A recent study using pan-lysyl oxidase inhibition in pancreatic cancer showed remodeling and crosslinking with fibrillar collagen matrices, reducing the tumor stiffness [14].…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic cancer, commonly referred to as PDAC, is a fatal disease with an incredibly poor prognosis and a 5-year survival rate of less than 10% [32]. Drug repurposing has shown great promise in the rapid identification of effective anti-PDAC drugs and several FDA-approved non-cancer drugs are currently being explored for the treatment of this lethal neoplasm [8].…”
Section: Discussionmentioning
confidence: 99%
“…Due to strong evidence for dysregulated ECM crosslinking in promoting fibrosis and the key roles of ECM crosslinking enzymes, therapeutics are actively being investigated to target TG, LOX, and LH proteins, with the most advanced drug molecules in phase I/II clinical trials ( Table 1 ) [ 69 , 70 , 71 , 72 , 73 , 74 , 75 , 76 , 77 , 78 , 79 , 80 , 81 , 82 , 83 , 84 , 85 , 86 , 87 , 88 , 89 , 90 , 91 , 92 ]. LOX therapeutics vary based on which LOX they target, and both small-molecule and antibody-based targeting approaches have been employed.…”
Section: Ecm Crosslink-based Therapeutic Strategies Drug Targets and ...mentioning
confidence: 99%